Effect of minimal processing and treatment with yerba mate on healthy potential and quality attributes of Granny Smith apples (INNOTEC, 2016)
The effect of the minimal processing with and without treatment with citric and ascorbic acids and yerba mate on the physicochemical, bioactive, microbiological and sensory characteristics of ‘Granny Smith’ apples was studied. Soluble solids and polyphenol contents, total aerobic mesophilic microorganism counts, sour taste and the browning sensory attribute were reduced by the minimal processing (without chemical treatment), while the sensory general appearance improved. When comparing the results obtained for the treated and untreated (control) freshcut apples, it was observed that the applied chemical treatment reduced the characteristic flavor of the apples and increased the sour taste, off-flavors and off-odors. However, the treatment was effective in controlling the browning development (L* increased, sensory general appearance improved and a* and sensory attribute browning decreased), in increasing the healthy potential (higher polyphenol and vitamin C content and antioxidant capacity), and maintaining the microbial counts similar to those obtained for the raw material.
Keywords: Fresh-cut fruits; Antioxidant capacity; Color